IMPLEMENTASI PANCA JIWA PONDOK DALAM PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN TA’MIRUL ISLAM SRAGEN - Muh. Nur Rochim Maksum; Bobby Hadi P; Ismail Lutfiriyanto; Deddy Ramdhani (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
The five souls of the Islamic boarding school are the spirit of the boarding school that makes the foundation and guidelines for behavior. The five five souls of the boarding school are not just a slogan but also a guideline for students and are character education that is formed for students, the process of forming the character of students based on the five five souls of the cottage through activities carried out every day. The purpose of this research is to describe the implementation of Panca Jiwa Pondok in the Character Building of the Santri of the Ta'mirul Islamic Boarding School in Sragen and describe the obstacles in the implementation of the Ta'mirul Islam Islamic Boarding School in shaping the character of the Santri of the Ta'mirul Islam Islamic Boarding School in Sragen. This type of research uses qualitative methods. In data collection techniques using observation, interviews, and documentation. Data analysis in this study uses data reduction, data presentation, and drawing conclusions. While the validity of the data test using triangulation of sources and techniques. The research location is at the Ta'mirul Islam Masaran Islamic Boarding School Sragen with the research subjects namely, Deputy Leaders of Islamic Boarding Schools, Student Care, 5th grade students of KMI.The results of this study are: 1. Implementation of the Panca Jiwa Pondok in the Character Building of the Ta'mirul Islam Islamic Boarding School students through the management of Pondok activities. Activities designed by the leader of the boarding school along with their caregivers and ustadz to shape the character of the students referring to the five souls. 2. Constraints experienced in the Implementation of the Five Souls of Pondok in the Character Building of the Ta'mirul Islamic Boarding School Santri, namely from the students and from the ustadz. The role of both greatly influences the ustadz, emulated from all aspects by the students. Lack of istiqomah some ustadz in giving examples to students, less often around checking the activities and supervision of students, some students still lack of awareness in obeying the rules of the boarding school, some students also have not fully obeyed the rules and also sometimes invite their friends to violate the rules, and the role of guardians of students also affect.